Analisis Kelayakan Kenaikan Harga dan Biaya Produksi Usaha Tani Padi selama Pandemic Virus Covid-19 di Wilayah Kecamatan Barat Kabupaten Magetan - Ali, Haidar (OECONOMICUS Journal of Economics, 2020)
This study aims to analyze the feasibility of increasing the price and production costs of rice farming in the West District of Magetan Regency. The results of the analysis show that the R / C analysis is 1.42,> 1. This means that the costs incurred are Rp. 1, can generate receipts of Rp. 1.42. Therefore, the feasibility of increasing prices and costs of rice farming in the West District of Magetan Regency is still considered feasible because it still provides benefits for rice farmers.